Eugenio Coseriu : Beyond Structuralism - Kabatek, Johannes (De Gruyter, 2023)
Eugenio Coseriu counts among the most important linguistic scholars of the second half of the 20th century. He is known mainly as a structuralist and a Romance linguist, but his work is in fact far more expansive in scope, including a comprehensive linguistic theory as well as writings on a wide range of issues, from semantics, syntax, typology, variational linguistics, language change, pragmatics and text linguistics to Vulgar Latin, the history of the philosophy of language and the history of Romance linguistics. Coseriu's thought is founded on solid philosophical principles, and his life brought him into contact with a number of different academic traditions and cultures. However, for a variety of reasons (among which, the languages in which he tended to publish: Spanish, Italian, French and German), knowledge of his thought is rather marginal in the Anglo-American world. This book aims to go some way to addressing this situation by offering an overview in English of Coseriu's main contributions to linguistics, and indeed to other disciplines. It is of general interest for the study of linguistics, the history of linguistics, and the philosophy of language, as well as for a broader reading public.